TA'LĪM AL-MUHĀDATSAH WA MUSYKILĀTUHU LADĀ AN-NAṬIQĪNA BI LUGĀT UKHRĀ - Laila Ahmad (UIN ANTASARI, 2020)
ABSTRACT The objectives of this study are: to find out how muhadatsah learning includes planning, implementation and assessment. Knowing what problems are faced by students and teachers in muhadatsah learning, and what Arabic teacher solutions are in overcoming problems faced by students at MTs Negeri 6 Barito Kuala and MTs Pondok Pesantren Dakwah Islamiyah. This research is a type of field research with a qualitative descriptive approach. In collecting data using observation and interview methods. Documentary, from primary and secondary data sources. Furthermore, it is analyzed using the analysis description technique, and the validity of the data is checked by using the technique, interpretation, triangulation of methods, and triangulation of data sources. The results showed that the implementation of the Arabic learning process was carried out in 3 stages of learning, the first was the preparation stage, at this stage the Arabic teachers at MTs N 6 Barito Kuala and at MTs Dakwah Islamiyah made planned preparations, as stated in the Learning Implementation Plan (RPP). . The two stages of the implementation of learning, at this stage the Arabic language teachers at the two madrasas could not fully carry out the learning process according to the lesson plans, because the situations and conditions of students and schools were not supportive. The learning method used in each lesson seems the same. The three stages of learning evaluation, at this stage the Arabic language teachers in the two madrasas only conduct an evaluation at the end of the lesson, which should be evaluated during the learning process and at the end of the lesson. Meanwhile, the problems faced are linguistic and non-linguistic problems. In linguistic problems, there are still many students who are not fluent in pronouncing hijaiyah letters and with vocabulary pronunciation, so they find it difficult to memorize mufradat, understand and apply the rules that have been learned. In non-linguistic problems, when the muhadtsah learning takes place, the teacher uses the mother tongue more as the language of instruction, as a result students are also not used to speaking Arabic, the students have little vocabulary, low interest and motivation, limited time, facilities and facilities. limited family, school and social environment that is less supportive. The implication of this thesis is that it becomes a means to overcome the problems of speaking Arabic skills at MTs N 6 Barito Kuala and at MTs Da'wah Islamiyah, and expects all parties, especially Arabic teachers to create a more accustomed environment to use.